Les partenariats éducatifs, vecteurs d’accompagnement du changement ? - Jehanne De Grasset (Éducation et Socialisation)
The recent history of education policy in France gives great importance to the development of collaborative practices within educational partnerships. The coordination of educational actors in the same territory is considered to be a vector of educational success. From an institutional point of view, the accumulation of projects induces a necessary renewal of the professional culture of educators. At work level, many studies confirm that it is when educational partners have some affinity that partnerships tend to develop.This article provides an overview of institutional reforms. Then it presents the case study of one educational partnership - le Projet Educatif de Territoire (PEdT). This project (PEdT) is part of the current reform of school timetable. In order to apply the institutionnal injunction, the discussion presents the key elements of support to the implementation of PEDT in terms of methodological and organizational devices.